Establishing legitimacy: Analysing legitimation strategies in WHO’s anti-smoking discourse - Hala Shaker Hammad (Universitas Syiah Kuala, 2026)
Children spend almost one-third of their day in schools, and much of the peer pressure arises in this educational setting. In September 2023, the World Health Organisation (WHO) released two publications to urge schools around the world to take the necessary steps toward creating a smoke and nicotine-free environment and implementing policies that prevent young people from starting smoking. The language of such documents usually conceals a high level of legitimation and persuasion to reach the target audience and achieve the intended goals. Meanwhile, the organisation strengthens its legitimacy when its actions are perceived by the public as desirable, moral, or appropriate. Data for this study were obtained from two key documents, namely ‘Freedom from Tobacco and Nicotine: Guide for Schools’ and ‘Nicotine and Tobacco-Free Schools Toolkit’. Both documents were collected and downloaded from the official website of the WHO. The current study uses the Critical Discourse Analysis (CDA) approach to analyse the construction of legitimacy in the WHO’s latest anti-smoking publications with van Leeuwen’s legitimation strategies as its analytical tool. The analysis has identified the use of multiple legitimation strategies, and the results indicate that the smoking ban discourse shows a general authoritarian attitude. Moreover, there is a shift toward a more rational, practical, and school-centred stance, a switch from “fighting the bad” to “protecting the good”. The results emphasise the role of persuasive language in crafting policy documents to generate favourable outcomes and maintain the organisation’s legitimacy.